Chromatic dispersion measurement using the relative power of two beating frequencies - Al-Qdah, M. T.; Rashid, H. A.; Khazani, M.; Dimyati, K.; Ali, B. M. (2005)
A novel technique for measuring the accumulated chromatic dispersion (CD) in single-mode fiber (SMF) is presented. The technique measures CD by simultaneously launching pump and probe optical signals at omega(1) angular optical-frequency separation, and two phase-conjugated terms into the SMF. The relative power of the beat frequencies that appear after the photodetector at omega(1) and at 2 omega(1) is used to determine the net dispersion. This technique was successfully demonstrated using a semiconductor optical amplifier (SOA) as a phase conjugator in order to achieve a 20-dB relative power variation as a result of up to 1900-ps/nm CD change. (c) 2005 Wiley Periodicals, Inc.